Pengaruh Strategi Bisnis Terhadap Praktik Tax Avoidance Dengan Koneksi Politik Sebagai Pemoderasi - Angriani, Salsabila Risma; Silfi, Alfiati; Hanif, Rheny Afriana; Odiatma, Fajar (Program Pascasarjana STIE Amkop Makassar, 2023)
The purpose of this study is to examine the moderating role of political connections in the relationship between business strategy and tax avoidance practices. All manufacturing businesses companies on the Indonesia Stock Exchange between 2017 and 2021 made up the population. The samples in this research were 44 firms evaluated over 5 years, therefore the total sample totaled to 220. Purposive sampling was employed for the study's data collection, and multiple linear regression analysis was performed using SPSS version 25 for data analysis. This research shows that Tax Avoidance is not impacted by the Prospector Business Strategy variable. Tax Avoidance may be affected by the business strategy of the defender. Tax avoidance is unaffected by political connections made by a prospector's business strategy. Defender Business Strategy with Political Connections as a Moderations has an effect on Tax Avoidance. Keywords : Tax Avoidance, Prospector Business Strategy, Defender Business Strategy, Political Connections